Tantangan globalisasi dan politik terhadap tradisi konstitusi Indonesia: Implikasi terhadap sistem ketatanegaraan - Syayyidah, Liza Elyvia Nur (Maliki Interdisciplinary Journal, 2026)
Constitutional tradition serves as an essential foundation in the state system, encompassing governmental practices, unwritten norms, conventions, and precedents that complement the written constitution. This study focuses on analyzing the concept of constitutional tradition, identifying its forms in Indonesia, comparing its implementation across various legal systems, and examining the challenges and dynamics it faces. By employing a library research method with a qualitative approach, this study reviews relevant literature related to constitutional tradition. The findings reveal that Indonesia’s constitutional tradition has evolved from the independence period to the reform era, characterized by its adaptability to changing times. The main challenges include the ambiguity of its legal status, the influence of globalization, socio-political dynamics, and the low level of public awareness. This research contributes theoretically to the development of constitutional law studies and provides practical benefits for deepening the understanding of Indonesia’s state system in a comprehensive and contextual manner.